Chronic disease comorbidities among middle-aged and elderly Chinese population with different depression levels: a network analysis on 2018 CHARLS data - Qiaofeng LI; Yilong YAN; Yuehan HE; Yongtai LI; Guowu DING (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the chronic disease comorbidities among middle-aged and elderly Chinese population with different depression levels and provide a scientific basis for optimizing depression screening and chronic disease prevention and treatment. MethodsData from 14 222 middle-aged and elderly individuals aged ≥ 45 years old were collected from the 2018 China Health and Retirement Longitudinal Study (CHARLS). A complex network model was used to analyze the patterns of chronic disease comorbidities in middle-aged and elderly population with different depression levels, and Gephi 0.10.1 software was used to visualize the chronic disease comorbidity network. Results Among the 14 222 middle-aged and elderly Chinese individuals, 7 020 had chronic disease comorbidities, with a comorbidity rate of 49.36%. There were 9 066 (63.8%) individuals without depression, 4 141 (29.1%) with mild depression, and 1 015 (7.1%) with severe depression. The number of chronic disease comorbidities was 3 841, 2 463, and 716 among those without depression, with mild depression, and with severe depression, respectively, and the comorbidity rates were 42.37%, 59.48%, and 70.54%, respectively. The comorbidity rate increased with the severity of depression (χ2trend = 537.35, P < 0.001). The proportions of individuals with 2, 3, and ≥ 4 chronic diseases were 43.7% (1 679/3 841), 26.5% (1 016/3 841), and 29.8% (1 146/3 841) among those without depression; 34.2% (843/2 463), 26.1% (644/2 463), and 39.6% (976/2 463) among those with mild depression; and 28.2% (202/716), 22.2% (159/716), and 49.6% (355/716) among those with severe depression, respectively. Gamma correlation analysis showed that the number of chronic disease comorbidities increased with the severity of depression (Gamma = 0.209, P < 0.001). The comorbidity pattern of hypertension & dyslipidemia had the highest prevalence (9.22%) among individuals without depression, while the comorbidity pattern of gastrointestinal or digestive system diseases & arthritis or rheumatism had the highest prevalence among those with mild (16.95%) and severe (24.33%) depression. Network analysis results showed that the absolute network densities of the chronic disease comorbidity networks were 11.46, 16.24, and 20.30 for individuals without depression, with mild depression, and with severe depression, respectively, and the absolute network density increased with the severity of depression. ConclusionThe chronic disease comorbidity rate was high among middle-aged and elderly Chinese population, and the patterns of chronic disease comorbidities differed among middle-aged and elderly population with different depression levels. The chronic disease comorbidity rate increased with the severity of depression.